2020
DOI: 10.31235/osf.io/e2x69
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Use of Vocabulary Learning Strategies by EFL and EAP Undergraduate University Learners’ in the Iraqi Context

Abstract: Vocabulary learning is an essential part of foreign or second language learning. This study aims at identifying the most and least common strategies that are used by Iraqi English as a foreign language (EFL) majors and English for academic purposes (EAP) learners. Also, determine the differences that are in EFL and EAP students' vocabulary learning strategy (VLS) use as well as exploring EFL and EAP students' views and difficulties. The study samples were 100 undergraduate learners (50 EAP learners and 50 EFL … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
0
0
0
Order By: Relevance
“…The results portrayed in Figure 3 justify our claim about the diversity of using VLSs among different students in either a different, or the same, context. This is consistent with previous research on VLSs (e.g., Schmitt, 1997, Gu, 2003Al-Qahtani, 2005;Al-Fuhaid, 2007;Ben Kridis, 2023) revealing that language students typically use a different number of VLSs and they sometimes prefer some VLSs, but not others. The current results indicate that EFL students were in favour of using metacognitive strategies, such as "Using English language media", "Using spaced word practice to revise vocabulary", and "Studying the word over time", more frequently than other types of strategies.…”
Section: Figure 3 Efl and Pyd Students' Frequency Of Use Of The Vlssupporting
confidence: 91%
See 1 more Smart Citation
“…The results portrayed in Figure 3 justify our claim about the diversity of using VLSs among different students in either a different, or the same, context. This is consistent with previous research on VLSs (e.g., Schmitt, 1997, Gu, 2003Al-Qahtani, 2005;Al-Fuhaid, 2007;Ben Kridis, 2023) revealing that language students typically use a different number of VLSs and they sometimes prefer some VLSs, but not others. The current results indicate that EFL students were in favour of using metacognitive strategies, such as "Using English language media", "Using spaced word practice to revise vocabulary", and "Studying the word over time", more frequently than other types of strategies.…”
Section: Figure 3 Efl and Pyd Students' Frequency Of Use Of The Vlssupporting
confidence: 91%
“…Females used note-taking strategies more frequently than males, but males used the "writing new words in English class notebook" more than females. In addition, Al-Qahtani (2005) found that female students, more often than male students, depend on "writing example sentences using the new word", "writing down the pronunciation of the new words", "grammatical organisation of the new words", and "repeating a sentence in which the word is used". In short, the results showed that discovery and consolidation categories were more frequently used than other types of VLSs.…”
Section: Literature Reviewmentioning
confidence: 99%